English learning strategies that boost the development of communicative skills of pre-school students level 2 in San Jose La Salle de Guayaquil. - Tumbaco Vega, Gianella Tamara (2017)
The main goal of this research project is to determine English learning strategies that boost the development of communicative skills of pre-school students level 2 in San Jose La Salle de Guayaquil. The specific objectives are to define English learning strategies for young learners and to identify how to boost the development of communicative skills in pre-school children. The research method in this study was a quantitative approach. The data collection was made with a survey to know about students’ learning experiences and through observations for both teachers and students to asses learners’ communicative abilities and to determine teachers’ techniques and strategies. Observations we re recorded in rubrics. It is concluded that the poor use of English learning strategies affects students’ communicative skills since they are not involved in activities that boost their communicative skills.